A guide to mental health for early years educators : putting wellbeing at the heart of your philosophy and practice - Moxley, Kate (New York : Routledge, 2022)
"This practical and accessible guide tackles the challenges that busy childcare educators face with their mental health in what is a wonderful, rewarding, but often exhausting role. Drawing from 'day-in-the-life' experiences and case studies, this book sets out high-quality staff wellbeing practices that can revolutionise the way childcare practitioners approach their job and their own health. Chapters guide the reader through a process of reflection and development, encouraging and empowering them to create a workplace culture that positively contributes to their personal wellbeing. This book: Focuses on the realities of early years education, combining the authors' lived experience with examples of real-life practice; Encourages educators to think and feel positively about themselves; to identify the individual skills, strengths and talents they bring to their work; Can be used individually or collaboratively by team members, with guidance on creating a positive workplace culture with a shared vision, core values and beliefs. Essential reading for anybody who finds that the job they love can sometimes leave them feeling worn out, stressed and depleted, this book has been written to enrich the lives of all training and practising early years educators"--
Part 1. Laying the foundations of our philosophy -- Part 2. A philosophy for wellbeing.
Keywords: Early childhood educators -- Mental health; EDUCATION / General; EDUCATION / Preschool & Kindergarten; EDUCATION / Professional Development